Aging parents’ and middle-aged children’s evaluations of parents’ disability and life problems - Lee, Hyo Jung (2021)
This study examined discrepancies in aging parents’ and middle-aged children’s evaluations of aging parents’ problems and how these discrepancies were associated with relationship characteristics. Using data from the Family Exchanges Study (dyad N = 331), discrepancies in the parents’ disabilities and life problems reported by parents and their offspring were examined. Children reported a greater number of disabilities and life problems in their parents’ lives than parents did. The discrepancy in the number of disabilities was associated with the frequency of phone contact, but not the frequency of in-person contact between generations. Findings confirm the gap in the evaluations of parents’ problems between generations, indicating that children may overestimate their parents’ problems, whereas parents may underreport their own problems. Frequent phone calls between aging parents and middle-aged children seem to play a positive role in conveying aging parents’ problems. The gap in knowledge of parents’ problems may lead to unmet needs and/or undesirable support exchanges between parents and offspring. Future research needs to consider both generations’ reports and to develop reliable methods to assess parents’ problems.